Minimally invasive treatment of the cyst of the canal of Nuck with the laparoscopic total extraperitoneal approach - Ülkü Mete Ural; Neriman Şengül; Elif Betül Esmer; Elif Aydın; Selma Erdoğan Düzcü (Northwestern Medical Journal, 2025)
The cyst of the canal of Nuck (CCN) is an extremely rare pathology that occurs as a result of the inability to obliterate the processus vaginalis. No standard therapeutic procedure currently exists, and the condition remains unfamiliar to gynecologists. In this report, we aimed to discuss the treatment of CCN with a minimally invasive method. A 33-year-old woman diagnosed with the CCN was treated with a laparoscopic total extraperitoneal approach with the best postoperative recovery. Awareness of CNN is critical for appropriate diagnosis and management. The classic treatment is excision of the cyst and closure of the inguinal ring as an inguinal hernia operation. The laparoscopic total extraperitoneal approach is a minimally invasive and effective treatment method that can be applied as an alternative to classical surgical treatment.